Effectiveness of nutrition movement counseling in the first 1000 days of life on knowledge and attitude of pregnant women - Rachman, Sandy Nurlaela; Alfi, Nur Mufidah; Fairuza, Filda (Institute of Computer Science (IOCS), 2025)
Abstract: The Indonesian government implements the First 1000 Days Movement (HPK), to improve nutritional status during pregnancy and breastfeeding, aiming to support brain development and the immune system from pregnancy until a child’s first year. This study aims to determine the extent to which nutritional counseling for the First 1000 Days of Life impacts the knowledge and attitudes of pregnant women. A quasi-experimental design with pre-test and post-test groups was used, involving 60 pregnant women. Knowledge and attitudes were measured before and after counseling. Data were analyzed using the independent t-test. The results of this study indicate that the knowledge of pregnant women in the pre-test was classified as poor for 34 people (56.7%) and sufficient for 23 people (38.3%). After being given counseling, the knowledge category became good for 32 people (53.3%). In terms of attitudes, the pre-test showed the category of poor for 35 people (58.3%). After counseling, the attitudes of respondents were in the good category for 32 people (53.3%). The effectiveness of counseling nutritional education in the first 1000 days of life on knowledge (p value 0.000 < 0.05) and attitudes of pregnant women (p value 0.000 < 0.05). The conclusion of this study is that it is effective in changing the knowledge and attitudes of pregnant women, so there is a need for enhancing the capacity of health educators is essential to deliver impactful education and promote positive behavioral changes in support of the HPK Movement.